2002
DOI: 10.1002/jmri.10175
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance histology for morphologic phenotyping

Abstract: Magnetic resonance histology (MRH) images of the whole mouse have been acquired at 100-micron isotropic resolution at 2.0T with image arrays of 256 ϫ 256 ϫ 1024. Higher resolution (50 ϫ 50 ϫ 50 microns) of limited volumes has been acquired at 7.1T with image arrays of 512 ϫ 512 ϫ 512. Even higher resolution images (20 ϫ 20 ϫ 20 microns) of isolated organs have been acquired at 9.4T. The volume resolution represents an increase of 625,000ϫ over conventional clinical MRI. The technological basis is summarized th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
93
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(93 citation statements)
references
References 14 publications
(14 reference statements)
0
93
0
Order By: Relevance
“…Imaging in the mouse requires significant hardware and sequence upgrades compared with standard human clinical scanners. However, despite the technical hurdles involved in mouse imaging, several mouse imaging centers have had success in imaging mouse brains with high neuroanatomical resolution [108][109][110][111][112][113], including ours at the Mouse Imaging Centre at the Hospital for Sick Children in Toronto [93,94,114].…”
Section: Discoveries Of Neuroanatomical Abnormalities In Mouse Modelsmentioning
confidence: 99%
“…Imaging in the mouse requires significant hardware and sequence upgrades compared with standard human clinical scanners. However, despite the technical hurdles involved in mouse imaging, several mouse imaging centers have had success in imaging mouse brains with high neuroanatomical resolution [108][109][110][111][112][113], including ours at the Mouse Imaging Centre at the Hospital for Sick Children in Toronto [93,94,114].…”
Section: Discoveries Of Neuroanatomical Abnormalities In Mouse Modelsmentioning
confidence: 99%
“…The COS study extends the use of MRM beyond that of previous studies (Delnomdedieu et al, 1996;Lester et al, 2000;Johnson et al, 2002), because MRM was used to identify major sites of COS neurotoxicity, and the information gained from MRM positively influenced the outcome of our functional and mechanistic studies.…”
Section: Introductionmentioning
confidence: 92%
“…Magnetic resonance microscopy is based on the same principles of MRI (Wheeler and Withers, 1996), but allows for higher resolution and sensitivity (Johnson et al, 2002). Higher resolution is achieved by the use of encoding gradients that are at least 5X-100X higher than those of clinical human MRI systems (Johnson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRH complements more traditional methods of histology in four unique ways-MRH is non-destructive; MRH exploits unique contrast mechanisms of water in the tissue; MRH is three-dimensional; and MRH is inherently digital, which makes it possible to readily share morphologic data over the Internet. A number of authors have demonstrated the utility of MRH in the mouse brain (Benveniste et al, 2000;Johnson et al, 2002a;Kovacevic et al, 2005;Ma et al, 2005;MacKenzie-Graham et al, 2004). However, comparing results between these studies is difficult because a wide range of acquisition strategies with varied tissue contrast has been employed.…”
Section: Introductionmentioning
confidence: 99%